Data Mining Applications Using Artificial Adaptive Systems - Tastle, William J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
none
Assessing Post-Radiotherapy Treatment involving Brain Volume Differences in Children -- J-Net: an Adaptive System for Computer-Aided Diagnosis in Lung Nodule Characterization -- Population Algorithm: A New Method of Multi-Dimensional Scaling -- Semantics of Point Spaces through the Topological Weighted Centroid and Other Mathematical Quantities -- Meta Net: A New Meta-Classifier Family -- Optimal Informational Sorting: The ACS-ULA Approach -- GUACAMOLE: A New Paradigm for Unsupervised Competitive Learning -- Spatiotemporal Mining: A Systematic Approach to Discrete Diffusion Models for Time and Space Extrapolation.
Keywords: Computer science; Data structures (Computer science).; Data mining; Artificial intelligence; Biometrics; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Data Structures; Biometrics